2023
DOI: 10.47536/jcrm.v12i2.581
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of whales and dolphins in Pakistan with reference to fishers’ knowledge and impacts

Abstract: This paper reports the findings of a project (Cetacean Conservation Pakistan) launched in 2004 with a view to: (a) undertaking quantitative surveys to determine the variety and abundance of species present; (b) working with local fisher communities to collate local knowledge and promote public awareness; and (c) promoting a marine cetacean conservation strategy and measures. Boat-based surveys for live animals and shore surveys for beachcast specimens have confirmed the presence of twelve species of whale and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…In neighbouring India, Jayasankar et al (2008) identified five of the six species of marine cetaceans (Indian Ocean humpback dolphin, spinner dolphin, bottlenose dolphin, long-beaked common dolphins and Indo-Pacific finless porpoise) using molecular identification techniques. By contrast, using boat-based surveys, Gore et al (2012) found that spinner dolphins (which were typically found offshore along the Balochistan coast) and Indian Ocean humpback dolphins and Indo-Pacific finless porpoises (most frequently found near-shore along the Sindh coast) were the more abundant species. This highlights that beach surveys are an important and effective method for determining species presence/absence and certain life history information such as sex and age of stranded animals.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…In neighbouring India, Jayasankar et al (2008) identified five of the six species of marine cetaceans (Indian Ocean humpback dolphin, spinner dolphin, bottlenose dolphin, long-beaked common dolphins and Indo-Pacific finless porpoise) using molecular identification techniques. By contrast, using boat-based surveys, Gore et al (2012) found that spinner dolphins (which were typically found offshore along the Balochistan coast) and Indian Ocean humpback dolphins and Indo-Pacific finless porpoises (most frequently found near-shore along the Sindh coast) were the more abundant species. This highlights that beach surveys are an important and effective method for determining species presence/absence and certain life history information such as sex and age of stranded animals.…”
Section: Discussionmentioning
confidence: 81%
“…DNA analysis showed that four of 24 samples that yielded DNA were misidentified in the field (Table 1), which could be attributed to progressive training and/or the fact that these carcasses were heavily degraded. There were three species confirmed using DNA that had not been observed during the boat-based surveys by Gore et al (2012). These were pantropical spotted dolphin, long-beaked common dolphin and Bryde's whale.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations